METHODICAL APPROACHES TO THE ASSESSMENT OF RESOURCE POTENTIAL AND THEIR IMPACT ON THE TRANSPORT SYSTEM OF UKRAINE - IRTYSHCHEVA, Inna; STEHNEI, Marianna; KRAMARENKO, Iryna; BOYKO, Eugenia; NADTOCHII, Iryna; SIRENKO, Ihor; HRYSHYNA, Nataliya; ISHCHENKO, Elena (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Today, the transport system plays a vital role in ensuring the socioeconomic development of the country, and it optimizes various flow processes related to transportation. The effectiveness of the functioning of the transport system depends on the use of organizational and innovative reserves, which acquires particular importance in countering Russian aggression. The destruction of the infrastructure, which is observed in Ukraine as a result of the Russian invasion, additionally actualizes the need to study issues related to the development of the transport system and the restoration of transport potential to ensure production processes and systematize flow processes in the socioeconomic sphere.The purpose of writing the article is the process of forming methodical approaches to assessing resource potential and their impact on the transport system of Ukraine.The proposed methodical approaches to the evaluation of the relationships between the parameters of the transport potential of Ukraine are based on the interpretation of the category "transport potential" by distinguishing its main parameters - resource provision and functioning results, between which there is a relationship, namely: the level of resource provision forms the operating results. Resource support is proposed to be characterized by statistical indicators that reflect material, human, and investment resources, and the results of functioning - by the value measurement of the volume of products sold by the type of economic activity "Transport, warehousing, postal and courier activities". A correlation dependence between the volume of products sold in the transport system and the corresponding indicators of resource provision has been proven.It has been proven that capital investments have the most significant influence on the increase in the value of the results of the functioning of the transport sector. The functional form of the constructed correlation equations creates an economic-mathematical assessment of the actual state of the impact of material, human, and investment resources on the results of the functioning of the transport sector. Also, it provides an opportunity to structure resources to achieve the desired result and form forecasts of the development of the transport industry. It is possible to develop further the proposed methodical approaches in developing mechanisms for stimulating the gradual modernization of Ukraine's transport system, which will be especially relevant in the post-war reconstruction of the country's infrastructure and economy.
Keywords: methodical approaches; resource potential; transport potential; transport system; efficiency assessment